Effect Of Coiling Temperature On The Mechanical Properties Of Hot Rolled Multi Phase 800 Mpa Steel - Luciano Santos Marques; Túlio Magno Fuzessy de Melo; Vicente Tadeu Lopes Buono (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The influence of the coiling temperature after hot strip rolling on the microstructure and on the tensile and hole expansion properties of a 800 MPa multiphase steel was investigated. For the temperatures between 150°C and 600°C the microstructure consisted of a ferritic matrix with a dispersion of fine martensite-austenite (MA) and regions of degenerated upper bainite. In all cases the ferrite presented a heterogeneous mixture of polygonal, quasi-polygonal and acicular grains. The yield and tensile strengths showed a tendency of decreasing with the increasing coiling temperature, probably because of the larger fraction of MA particles at lower temperatures and higher fraction of quasi-polygonal ferrite at higher temperatures. The elongation was not significantly affected by the variation of coiling temperature. The average hole expansion ratio showed a maximum of 80% for the material coiled at 400°C and fell below 50% only for the coiling temperature of 150°C, probably due to the larger hardness difference between the ferrite matrix and the MA particles.